(untitled) (Nordic Journal of African Studies, 2005)
The paper undertakes a study of animal metaphors in the Yorùbá language with a view to highlighting the stylistic and communicative potentials of these metaphors. To achieve the set objective, the animals – domestic and wild – involved in metaphors and their individual distinctive characteristic features that motivate their metaphorical interpretations are highlighted. The paper also discusses the sources of animal metaphors, which are said to be located in three areas, namely: the Yorùbá naming culture, animal characteristic habits and behaviour, and the Yorùbá poetry. In discussing the metaphorical processes involved in the interpretation of animal-related metaphors, a two-dimensional approach is adopted: stylistic and cultural. In the first, the semantic features of animals involved in metaphors are decomposed into semantic markers that are of two types. The first is the High Priority Semantic Markers (HPSM), which determine the cognitive/conceptual meaning of the metaphors, and the second is the Low Priority Semantic Markers (LPSM), which determine the secondary metaphorical interpretation. Animal metaphors involve transference of meanings, and whatever meanings or interpretations are assigned to a particular animal metaphor, are culture and context dependent. The paper concludes with stylistic and communicative functions of animal metaphors, with the submission that stylistically animal metaphors contribute to aesthetics and poetic elegance of literary texts through their lexical tones, which can be stylistically manipulated. They are also being used as a new or additional mode of expression in both literary and routine communication.